Awareness Regarding Child Abuse among Mothers Attending a Pediatric Clinic of a Tertiary Level Hospital, Kathmandu - Adhikari Mishra, Tulashi; Bhattarai, Tilarupa (Journal of Institute of Medicine Nepal, 2019)
Introduction Child abuse constitutes all forms of physical as well as emotional maltreatment resulting in harm to the child’s health and overall development. Parental awareness plays a significant role in the prevention of child abuse. The objective of this study was to find out the awareness of mothers regarding child abuse. Methods This descriptive cross sectional study was carried out among mothers attending a Pediatric Outpatient Department of Tribhuvan University Teaching Hospital Kathmandu, Nepal. A total of 162 mothers having their children of aged one to 16 years were selected as a sample using non-probability convenient sampling technique. Data was collected by face to face interview using semi-structured interview schedule. Results Findings of the study revealed that majority of mothers could state different types of abuse as physical abuse (72.8%), psychological abuse (78.4%), sexual abuse (71.6%), but 53.1% of mothers were aware about neglect, 48.8% of mothers considered that relatives could abuse their child. In total, 49.1% of mothers had moderately adequate, 26.4% had inadequate and 23.9% had adequate level of awareness regarding child abuse. No significant association was noted between the level of awareness and mothers’ age, ethnicity, religion and occupation. The level of awareness of mothers was significantly associated with nuclear family type (p=0.03). Conclusion The mothers are aware of child abuse at moderate level. Conducting awareness programmes in community, regarding child abuse focusing on child neglect is recommended.